Effects of a heparin-binding protein on blood coagulation and platelet function - Kaiser, Phoebe; Harenberg, Job; Hoppensteadt, Debra; Walenga, Jeanine M.; Huhle, Günter; Giese, Christina; Prechel, Margaret; Fareed, Jawed (Seminars in thrombosis and hemostasis, 2001)
Thieme E-Books & E-Journals